Potential of Construction and Demolished Wastes as Pozzolana. (2016) - Antony, Jiji; Nair, Deepa G.
Abstract: The construction and demolition (C&D) wastes constitute 25% of the solid waste generation in India. A large proportion of these wastes are disposed off as landfill leading to severe social and environmental problems. Environmental considerations are pushing the industry towards more sustainable practices which leads less energy intensive blended cements in construction. This paper examines the possibility of using the finely ground C&D wastes as cementitious material. The C&D wastes are categorised as processing waste and demolition waste. The processing wastes used in this study are saw dust ash and roof tile powder. The demolition wastes used for this study are concrete waste and laterite waste. The results obtained confirmed the pozzolanic activity of both processing waste and demolition waste.